Information content of analysts' report: A literature survey - Mohd Thas Thaker, Hassanudin *; Mohamad, A.; Mustaffa Kamil, N. K.; Duasa, J. (Faculty of Economics, Universitas Islam Indonesia, 2018)
The objective of this paper is to survey the literature on the information content of analyst report from three essential dimensions, namely, target price, earnings forecast and trading volume. The method employed is following the qualitative approach by reviewing and examining the past literature from the view of theoretical and empirical researchers. The initial result from existing literature, reveals that the research in analyst report mainly focused on empirical research rather than theoretical perspective. Secondly, there no clear consensus on the consistency of results regarding how well the information contents involving target price, earnings forecast and trading volume influencing the stock return. Thus, the views whether analyst report transmitting information to the investors still remain unambiguous when making an investment decision. This study is expected to enrich the existing literature in the area of analyst report and propose several areas for future researchers related to this topic.